TA: Tonja Bowen Bishop
TA: Tonja Bowen Bishop
TA: Tonja Bowen Bishop
Problem 1
For parts (a)-(g), please refer to the relevant sections in the handouts/textbooks.
(h) False. With the knowledge of the distribution of a statistic under
the null hypothesis, we can calculate only , but not :
(i) False. In particular, there are hypothesis tests for which one can
form a GLRT where no optimal test exists, so GLRT could not be optimal
in that case.
(j) Yes. Hypothesis tests are typically constructed by using a test
statistic T . The null hypothesis is rejected if T lies in some interval or if T
lies outside of some interval. The interval is chosen to make the test have
a desired signicance level. This procedure is in essence the same as the
construction of the condence interval.
(k) Recall that and are calculated under dierent distributions
(under the null and under the alternative hypothesis). There is no reason
that it always must be + = 1; although it is possible under some special
circumstances. Also, in general, it is not possible = = 0; again in some
cases we might have = 0 or = 0, but in many cases neither is possible.
NOTE: We might have some cases that = = 0 under very special
and unrealistic situation (can you think of an example of such case ?), and
in that case, the hypothesis test becomes trivial and uninteresting. (why ?)
Problem 2
(a) The probability of committing a Type I error is calculated as
follows:
P (Type I error) = P (reject H0 jH0 is true)
= P (Y
3:20j = 1)
Z 1
=
e y dy
3:20
= 0:04
= 4=3 is
and
in terms of k:
= k
0
2
= k2
2k + 1
Note that we were able to write down expressions for and because
with only 1 observation x; we knew that x had to be our statistic, and
furthermore our test would be of the form reject H0 for x < kbecause we
are more likely to have observed a small x if HA is true.
min( + ) = min(2k 2
k
@(2k 2
So
2k + 1)
= 4k
@k
is minimized at k = 1=2:
ii)
1
4
1
4
2k + 1)
2=0
= 12 :
iii) With k = 1=2, the testing procedure is then to reject the null for
x < k = 1=2: So we do not reject the null for x = 0:6
(b)
Z
f0 (x)dx =
this implies k =
0:1:
0:10 ?]
ii) Then
(2
2x)dx
0:1
x2 ]1p0:1
p
2 0:1
= [2x
= 1:1
f (x1 ; :::; xn j ) =
i=1
f (xi j )
1
p e
i=1 2
= (2 )
n
2
)2
(xi
2
1
2
P
(xi
)2
Then we have
T
(2 )
n
2
(2 )
1
2
= e
= enX
e
n
2
1
2
P
(xi 1)2
1 P 2
xi
2
P
( 2xi +1)
n
2
so we use
0:005 = Pr X > c j = 0
0
X 0
c 0
= Pr @ q
> q j
1
n
= Pr Z >
1
n
nc
= 0A
nc = 1:65, so c =
the nal form of our test is that we reject the null if X >
Problem 5
(a) H0 :
X
if
= 7 versus H1 :
1:65
p .
n
Thus
1:65
p .
n
= 6.
(b) The
And under the null
p test statistics is sample mean: T = X: p
N (7; 1= 10);and under the alternative X N (7; 1 10): We reject H0
1
1
p
(0:05)
10
1
= 7 p (1:65)
10
= 7 (0:32)(1:65)
= 6:47
X < 7
T =
X
p
S= n
t(10
1)
we reject H0 if
X
p
S= n
6:2 7
p
p
1:5= 10
<
t9 ( ), where
is a signicance level
,
=
2:5 <
So we reject H0 :
H1 :
(e) In this case, the test then becomes two-sided [H0 : = 7 versus
6= 7], so all the procedures used before should be modied accordingly.
Problem 6
Suppose Xi
N ( X ; 1); i = 1; :::; nX and Zj
N ( Z ; 1); j = 1; :::; nZ
and all the observations are independent. You want to test the hypothesis
that the means are equal against the alternative that they are not. Use the
statistic
T =p
(X
Z)
1=nX + 1=nZ
(a) The test statistic T can take any real number, and if the absolute
value of T is su cientlydierent from 0; we will reject the null hypothesis
that the means are equal.
"
(X
V ar[T ] = V ar p
Z)
1=nX + 1=nZ
1
V ar[X Z]
1=nX + 1=nZ
1
V ar[X] + V ar[Z] (independence)
1=nX + 1=nZ
1
1 X
1 X
V ar
Zj
Xi + V ar
1=nX + 1=nZ
nX
nZ
1
1
1
nX (1) + 2 nZ (1)
1=nX + 1=nZ
n2X
nZ
!
1
1
1
+
nX +nZ
nX
nZ
n n
=
=
=
=
nX nZ
nX + nZ
nX + nZ
nX nZ
= 1
So T
N (0; 1):
(c) Since the distribution of the test statistic T is the standard normal under the null, we reject the null when jtj > z =2 :
Problem 7
(a) Consider the test statistic T =
and
(nY
SY2 is
1)SY2
dened analogously.
2
Y
2
(nY
1) ,
2 =
where SX
We know that
n
Y
P
i=1
nX 1
2
(nX 1)SX
2
X
2
X
2,
Y
so we can rewrite T as
n
X
P
Xi
i=1
2
(nX 1)
n
X
P
Un-
2
(nX 1)SX
2 (n
1
)
X X
2
(nY 1)SY
2 (n
Y 1)
Y
Xi
1; nY
=
i=1
Yi
= 8:75. So T =
118=5
8:75=3
and
2
SX
,
SY2
1) > c) =